The impact of coordination-based movement education model on balance development of 5-year-old children - Esen, Hüseyin Tolga; Güçlüöver, Aziz; Kurnaz, Mert; Altinkök, Mustafa (Frontiers in Psychology, 2023)
With this study, it was aimed to examine the effect of coordination-based movement education model on the development of balance in five-year-old children. The research was designed with a control group pretest-posttest design, which is one of the quasi-experimental research models. The research group consists of a total of 42 (n=20 experimental n=22 control) five-year-old children formed by using the convenient sampling method, which is one of the purposeful sampling methods. Each participant’s age, body weight, body length and lower extremity limb lengths were measured. As a data collection tool and used the three-part Y Balance Test (YBT) platform, which was previously stated to have high reliability (ICC=0.85-0.93). Reach distances of the participants were measured in 3 directions, anterior posteromedial and posterolateral. YBT scores were determined by calculating the average and normalized values for lower extremity limb length for each reach direction of the obtained scores, and composite YBT scores were determined by taking the averages of anterior, posteromedial and posterolateral reach distance scores. In order to determine whether the collected data are suitable for normal distribution, Levene test was applied first and it was determined that p>0,05 for all parameters as a result of the test. Independent sample T test from parametric tests was used to determine the differences between groups. Paired-group T-test was used to determine within-group differences. According to the results of the research, it was found that the balance motor capacity levels between the experimental and control groups did not differ significantly compared to the pre-test, but there was a significant difference in all reach directions scores in favor of the post-test and experimental group compared to the control group and the pre-test. When the results of the right and left lower extremity ANT, PM, PL and Composite reach distances were examined according to gender, although there was no statistically significant difference, when the averages were considered, it was seen that all parameters were in favor of girls (p>0.05). As a result, it was concluded that coordination-based movement education model had a positive effect on the balance motor capacities of five-year-old children.